A new skipper from China: Notocrypta ariannae n. sp. (Lepidoptera, Hesperiidae) - Gallo, Enrico; Bozano, Gian Cristoforo (Zootaxa, 2017)
A new skipper species, Notocrypta ariannae n. sp., is described from C Sichuan, illustrated with its male genitalia and compared with the four other Notocrypta species found in China.